Collaborative Governance Dalam Penertiban Pertambangan Galian C Ilegal Di Kabupaten Kampar - Elisabet Panjaitan; Hasim As'ari (Jurnal Niara, 2025)
Observing that there are still many business actors who carry out mining activities without a permit in Kampar Regency which results in environmental damage and community unrest, there is a need for a collaborative process between stakeholders. This study aims to analyze collaborative governance in the control of illegal C mining in Kampar Regency and its obstacles. This study uses a descriptive qualitative research method. The theory used is the factor theory in the collaborative governance process by Schottle, which is 7 factors: willingness to compromise two or more parties, communication, commitment, mutual trust, transparency of information exchange, knowledge sharing and willingness to take risks. The results of this study found that collaborative governance in the control of illegal mining C was carried out informally with a willingness to compromise in the form of meetings and socialization, then communication by giving directions regarding licensing, then a commitment for mining business actors to carry out excavation activities by having permits, and mutual trust carried out by carrying out activities according to authority and responsibility, then the transparency of information exchange is carried out by sharing data about business actors, then sharing knowledge about the impact of mining that is not in accordance with the rules, as well as the willingness to take risks in the field in the collaboration process. Other obstacles faced in this collaboration process are policy changes regarding licensing authority, weak coordination between parties, as well as financing and budgeting